PENGARUH BUDAYA ORGANISASI DAN STATUS SOSIAL EKONOMI TERHADAP KOMPETENSI PROFESIONAL GURU DI SMA NEGERI 13 SURABAYA - Cahyono, Purwo (UNIVERSITAS NEGERI SURABAYA, 2013)
This study aimed to determine the influence of organizational culture and socioeconomic status on the teachers professional competency. This study was an explanatory research using a quantitative approach. The population covers 59 teachers at the 13th State Senior High School of Surabaya. Sample was 51 teachers with two different classes which determined using proportionate stratified random sampling technique, with Slovin formula. The Data were collected using questionnaires and documentations. The Analyzed of the data were quantitatively using simple and multiple linear regression. The hypothesis was tested using the t test and F test technique. Based on the research results, it was concluded that: (1) There is a partial influence of organizational culture on teachers professional competency, (2) There is a partial influence of socio - economic status on teachers professional competency, and (3) There are simultaneous influences of organizational culture and socioeconomic status on the teachers professional competency.